Household financialization: Sense and scale of this phenomenon on the example of Poland - Ryszard Kata; Justyna Chmiel (e-Finanse: Financial Internet Quarterly, 2017)
The subject of the study is the phenomenon of household financialization. In the first part of the article a sense of this situation and its influence on the different functioning areas of the households (income, expenses, financial decisions) is described. What is more, the positive and negative effects of this process for the households' financial stability were defined. The next part of the article contains an analysis of the households financialization processes in Poland in the years 2005-2015. On the side of household savings, the analysis included the level and the structure of financial assets. The second area of evaluation of the household financialization processes was bank debt analysis, including mortgage debt. In the elaboration comparative analysis was used, which means that Polish household structure of financial assets and the level of debt were compared to the European Union countries.
Keywords: D14; G20; 330; households financializaton; financial assets; bank loans